A concept analysis: Physical activity level - Fransiskus Xaverius Widiantoro; Friska Sinaga (Malahayati International Journal of Nursing and Health Science, 2020)
Background: A concept of physical activity level has been used wiely as a key variable in research. A clearly defined concept could help provide advance knowledge of the term and allow for analysis and clarification to ensure consistency in meaning and understandingPurpose: this concept analyses was examined the concept of physical activity levels that can be applied in clinical situation.Methods: Walker and Avant evolutionary method of concept analysis was used to collect and analyse the data. The CINAHL, MEDLINE, Ovid, and PubMed databases were searched for publications from 1990–2020. Search terms included physical activity, physical activity level, moderate-intensity of physical activity, and concept analysis. Data were analysed with particular focus on the attributes, antecedents and consequences of the concept.Results: Defining attributes of physical activity level were identified as personal to express number of daily physical activity (include intensity, frequency and duration) and to estimate a total of energy expenditure. Antecedents for physical activity to occur there should be living, conscious being to experience it, can movement or activity, and healthy. Consequences of physical activity levels viewed on a continuum from negative and positive.Conclusion: This concept analysis provided an in-depth analysis and clarification of physical activity levels. Studies needed to explore physical activity level for specific risk group likes high-risk of diabetes; behavior and psychological aspects influences physical activity level; trend and issues of physical activity level related with transcultural aspects; and government support to promote physical activity program.